Pengaruh Pertumbuhan Pendapatan Usaha, Perputaran Piutang dan Perputaran Persediaan Terhadap Peningkatan Laba Bersih PT. Mayora Indah Tbk - Putu Tirta Sari Ningsih; Nilam Nurcahya (Ilmu Ekonomi Manajemen dan Akuntansi, 2020)
The company always aims to increase the profit that it wants to obtain. one way to monitor the receivable turnover, can increase the company's business income. As well as always monitoring the supply of merchandise so that there is no deposition of manufactured goods. This study aims to determine the effect of operating revenue, accounts receivable turnover and inventory turnover against net income at PT. Mayora Indah Tbk. Net income comes from income, expense, profit and loss transactions. These transactions are summarized in the income statement. This study uses quantitative methods and uses secondary data on the financial statements of PT. Mayora Indah Tbk. The technical analysis of the data used in this study is the Classic Assumption Test, Multiple Regression Test, Hypothesis Test (t test and f test) and the Determination Coefficient Test using SPSS version 24. From the results of the f test data analysis can be seen f count ftabel (29.152 19.16) with a significant value of 0.033 0.05 that the independent variables simultaneously have a significant effect on net income. And partially (t test) variables of operating revenue and inventory turnover have a significant effect on net income but for accounts receivable turnover there is no significant effect on net income. Through testing the Determination Coefficient obtained Adjusted R Square (R2) of 94.4% net profit can be explained by the three independent variables, while the remaining 5.6% is explained by other variables outside the research model. Based on the results of the study, it can be concluded that operating revenue negatively affects net income, accounts receivable turnover has no effect on net income and inventory turnover has a positive effect on net income. While simultaneously the variables of business income, accounts receivable turnover and inventory turnover have a positive effect on net income.Keywords: Operating Revenue, Receivable Turnover, Inventory Turnover, Net Income.